Lean Regulation in Public Administration: Preconditions for Implementation and Main Content - I. I. Rakhmeeva; M. Yu. Andronov (Управленческие науки, 2025)
This article examines the application of lean thinking approaches in public administration. The relevance of this issue is driven by the state’s need to reduce the costs of both regulation itself and decision-making, a goal that is conceptualized in the Unified Plan for Achieving the National Development Goals of the Russian Federation until 2030 and beyond, up to 2036. The purpose of the paper is to substantiate the prospects of introducing lean regulation in public administration in Russia in the medium term. The research addressed several tasks, including a methodological comparison of approaches to collective regulation; defining the concept of lean regulation; and describing the effects of its implementation in public administration, with a focus on organizations in the financial sector. The authors employed a methodology based on theories of collective decision-making, lean management, public-private governance, and new public management. The information base included documents and data from legal reference systems and the official website of the Bank of Russia. The study outlines the future potential of applying the proposed approach. The results may be useful both to government authorities and the management of the Bank of Russia in their operations, as well as to researchers in the field of public administration as a theoretical foundation for applied work. Applying the principles and tools of lean regulation, as proposed by the authors, in public administration practice will improve the effectiveness of managerial decisions while taking into account the specific characteristics of individual sectors.